Aerophilic Surfaces for Sustained Corrosion Protection of Metals Underwater - Prado, Lucia; Hayek, Samer; Mazare, Anca Valentina; Erceg, Ina; Sarau, George; Christiansen, Silke; Kamaleev, Maksim; Wurmshuber, Michael; Lohbauer, Ulrich; Goldmann, Wolfgang; Virtanen, Sannakaisa; Tesler, Alexander (Advanced Functional Materials, 2024)
Corrosion and biofouling are wetting-related phenomena that limit the effective use of metals in aqueous media. Nonwettable surfaces can mitigate the adverse effects of wetting by minimizing contact with water. However, current achievements in this field fall short of meeting industrial requirements due to the short lifetime of plastrons. This study proposes a method to measure the protective sustainability of plastron. Superhydrophobic (SHS) and aerophilic (APhS) surfaces are constructed on lightweight aluminum and are initially analyzed by conventional goniometry, which show comparable values. However, the plastron that develops underwater is substantially different. While SHS exhibit unevenly broken plastron, APhS show uniform, continuous plastron. As an example of the sustained protective performance of plastron, the corrosion resistance of SHS and APhS is presented. Potentiodynamic polarization, impedance spectroscopy, and long-term immersion in seawater show a drastic enhancement in corrosion resistance, exclusively for APhS. In fact, almost no electrochemical signals are measurable, and no pitting corrosion is observed after 415 days of immersion in seawater. Conversely, SHS show no noticeable improvement and corrode faster than bare Al due to plastron loss. Since goniometric measurements do not provide information on plastron, it is essential to analyze the plastron for any non-wettable surface utilized underwater.<br
Keywords: air plastron; aluminum; Cassie–Baxter wetting; corrosion; superhydrophobic surfaces; underwater

Enhancing mechanical properties of ultrafine-grained tungsten for fusion applications - Wurmshuber, Michael; Doppermann, Simon; Wurster, Stefan; Jakob, Severin; Balooch, Mehdi; Alfreider, Markus; Schmuck, Klemens; Bodlos, Rishi; Romaner, Lorenz; Hosemann, Peter; Clemens, Helmut; Maier-Kiener, Verena; et al. (International Journal of Refractory Metals & Hard Materials, 2023)
Keywords: Ultrafine-grained; Grain boundary segregation engineering; Small-scale testing; Tungsten; Mechanical properties; Nuclear fusion

Helium-induced swelling and mechanical property degradation in ultrafine-grained W and W-Cu nanocomposites for fusion applications - Wurmshuber, Michael; Balooch, Mehdi; Huang, Xi; Hosemann, Peter; Kiener, Daniel (Scripta Materialia, 2022)

High-temperature nanoindentation of an advanced nano-crystalline W/Cu composite - Burtscher, Michael; Zhao, Mingyue; Kappacher, Johann; Leitner, Alexander; Wurmshuber, Michael; Pfeifenberger, Manuel; Maier-Kiener, Verena; Kiener, Daniel (Nanomaterials, 2021)
Keywords: Nanoindentation; W/Cu composite; Microstructure; Nanocrystalline; High-pressure torsion; kernfusionsrelevant

Impact of interfaces on the radiation response and underlying defect recovery mechanisms in nanostructured Cu-Fe-Ag - Wurmshuber, Michael; Frazer, David; Bachmaier, Andrea; Wang, Yongquiang; Hosemann, Peter; Kiener, Daniel (Materials & Design, 2018)
Keywords: Nanostructured materials; Radiation resistant materials; Defect-interface interactions; Nanoindentation; Severe plastic deformation; kernfusionsrelevant

Instantiations of Multiscale Kinship in Pressing‐Defect Distributions in Yttria‐Stabilized Zirconias by Powder Partitioning - Pereira, Raíssa Monteiro; Lohbauer, Ulrich; Schulbert, Christian; Göken, Mathias; Wurmshuber, Michael; Campos, Tiago Bastos Moreira; Thim, Gilmar Patrocínio; Mieller, Björn; Belli, Renan (Advanced Engineering Materials, 2024)
Modern dry pressing of ceramic powders using spray-dried granulates cannot avoid the occurrence of defects related to persisting inter- and intra-granulate interstitial voids. These constitute the parent defect size population limiting the application of polycrystalline ceramics in high-stress conditions. The mitigation of such defects could widen the range of application in technical and biomedical engineering, reduce the safety range for design, and extend the lifetime of components. Herein, the Weibull size-effect on strength in size-partitioned Yttria-stabilized zirconias (YSZ) feedstocks is used to explore the viability of changing the density distribution of granulate sizes as an effective strategy to obtain a denser particle packing that could reduce the size distribution of strength-limiting pressing defects. In a direct assessment of critical defect size using multiscale strength testing with a dataset of ≈1300 values, the success of such an approach in increasing the strength reliability for small volume components is demonstrated, along with its ultimate failure in altering the defect size distribution in sintered YSZ ceramics across several length scales. Finally, it is shown that granule morphology (spherical or dimpled) fails to affect the defect density and size distribution in YSZ ceramics.<br
Keywords: powder processing; pressing defects; strength; Weibull statistics; zirconia ceramics

Limpet teeth microstructure unites auxeticity with extreme strength and high stiffness - Oh, Sang Ho; Kim, Jin-Kyung; Liu, Yue; Wurmshuber, Michael; Peng, Xiang-Long; Seo, Jinsol; Jeong, Jiwon; Wang, Zhen; Wilmers, Jana; Soyarslan, Celal; Kim, Jongil; Kittiwirayanon, Boonsita; et al. (Science Advances, 2022)

Lower hardness than strength: the auxetic composite microstructure of limpet tooth - Wurmshuber, Michael; Wilmers, Jana; Kim, Jongil; Oh, Sang Ho; Kiener, Daniel (Acta Biomaterialia, 2023)
The limpet tooth is widely recognized as nature's strongest material, with reported strength values up to 6.5 GPa. Recently, microscale auxeticity has been discovered in the leading part of the tooth, providing a possible explanation for this extreme strength. Utilizing micromechanical experiments, we find hardness values in nanoindentation that are lower than the respective strength observed in micropillar compression tests. Using micromechanical modeling, we show that this unique behavior is a result of local tensile strains during indentation, originating from the microscale auxeticity. As the limpet tooth lacks ductility, these tensile strains lead to microdamage in the auxetic regions of the microstructure. Consequently, indentation with a sharp indenter always probes a damaged version of the material, explaining the lower hardness and modulus values gained from nanoindentation. Micropillar tests were found to be mostly insensitive to such microdamage due to the lower applied strain and are therefore the suggested method for characterizing auxetic nanocomposites.
Keywords: Biomaterials; Auxetic materials; Nanoindentation; Micromechanical modeling

Mechanical performance of doped W–Cu nanocomposites - Wurmshuber, Michael; Burtscher, Michael; Doppermann, Simon; Bodlos, Rishi; Scheiber, Daniel; Romaner, Lorenz; Kiener, Daniel (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2022)
Keywords: kernfusionsrelevant

Micro-Mechanical Fracture Investigations on Grain Size Tailored Tungsten-Copper Nanocomposites - Schmuck, K.; Burtscher, M.; Alfreider, M.; Wurmshuber, Michael; Kiener, D. (JOM Journal of the Minerals, Metals and Materials Society, 2024)
Tungsten-copper composites are used in harsh environments because of their superior material properties. This work addresses a tungsten-copper composite made of 20 wt.% copper, which was subjected to grain refinement by high-pressure torsion, whereby the deformation temperature was varied between room temperature and 400 °C to tailor the grain size. Deformation was performed up to microstructural saturation and verified by hardness measurement and scanning electron microscopy. From the refined nanostructured material, micro-cantilever bending beams with cross-sections spanning from 5 × 5 to 35 × 35 µm2 were cut to examine possible size effects and the grain size influence on the fracture behavior. Fracture experiments were performed in situ inside a scanning electron microscope by applying a quasi-static loading protocol with partial unloading steps. Inspection of the fracture surfaces showed that all cantilevers failed in an inter-crystalline fashion. Nevertheless, remaining coarser tungsten grains impacted the resultant fracture toughness and morphology. Cantilevers fabricated from the 400 °C specimen exhibited a fracture toughness of 220 ± 50 Jm2 . For the room temperature cantilevers, a fracture toughness of 410 ± 50 Jm2 was observed, which declined to 340 ± 30 Jm2 for cantilevers < 10 × 10 µm2, confirming a size effect. The increased fracture toughness is attributed to the delamination-like structures formed in the room temperature sample.
CRIS-Team Scopus Importer:2024-01-19

Novel Approach for Assessing Cyclic Thermomechanical Behavior of Multilayered Structures - Seligmann, Benjamin; Alfreider, Markus; Wurmshuber, Michael; Kiener, Daniel (Advanced Engineering Materials, 2023)
Keywords: copper; stress modeling; finite element modeling; thin films; thermomechanical fatigue

Open-cell tungsten nanofoams: Scaling behavior and structural disorder dependence of Young's modulus and flow strength - Zhao, Mingyue; Schlueter, Karsten; Wurmshuber, Michael; Reitgruber, Maria; Kiener, Daniel (Materials & Design, 2021)
Keywords: Mechanical properties; Microstructure; Tungsten; Nanoindentation; Nanoporous; kernfusionsrelevant

Recent advances in nanomechanical and in situ testing techniques: Towards extreme conditions - Kiener, Daniel; Wurmshuber, Michael; Alfreider, Markus; Schaffar, Gerald J.K.; Maier-Kiener, Verena (Current Opinion in Solid State & Materials Science, 2023)
Nanoindentation based techniques were significantly enhanced by continuous stiffness monitoring capabilities. In essence, this allowed to expand from point-wise discrete measurement of hardness and elastic modulus towards advanced plastic characterization routines, spanning the whole rate-dependent spectrum from steady state creep properties via quasi static flow curves to impact or brittle fracture. While representing a significant step forwards already, these techniques can tremendously benefit from additional or complementary input provided by in situ or operando experiments. In fact, by combining and merging these approaches, impressive advances were made towards well controlled nanomechanical investigations at various non-ambient conditions. Here we will discuss some novel experimental avenues facilitated by deliberate extreme environments, and also indicate how future improvements and enhancements will potentially provide previously unseen insights into fundamental material behavior at extreme conditions.
Keywords: Nanoindentation; Miniaturized mechanical testing; Fracture mechanics; Continuous stiffness measurement; kernfusionsrelevant

Small-scale fracture mechanical investigations on grain boundary doped ultrafine-grained tungsten - Wurmshuber, Michael; Alfreider, Markus; Wurster, Stefan; Burtscher, Michael; Pippan, Reinhard; Kiener, Daniel (Acta Materialia, 2023)

Strength ranking for interfaces between a TiN hard coating and microstructural constituents of high speed steel determined by micromechanical testing - Gsellmann, Matthias; Klünsner, Thomas; Mitterer, Christian; Krobath, Martin; Wurmshuber, Michael; Leitner, Harald; Ecker, Werner; Marsoner, Stefan; Maier-Kiener, Verena; Kiener, Daniel; Ressel, Gerald (Materials & Design, 2021)
Keywords: FEM simulation; Interface strength; Carbides; Coating adhesion; Micropillar

Tailoring ultra-strong nanocrystalline tungsten nanofoams by reverse phase dissolution - Zhao, Mingyue; Issa, Inas; Pfeifenberger, Manuel; Wurmshuber, Michael; Kiener, Daniel (Acta Materialia, 2020)
Keywords: Nanoporous tungsten; Selective phase dissolution; Microstructure characterization; Nanoindentation; kernfusionsrelevant

The effect of grain size on bubble formation and evolution in helium-irradiated Cu-Fe-Ag - Wurmshuber, Michael; Frazer, David; Balooch, Mehdi; Issa, Inas; Bachmaier, Andrea; Hosemann, Peter; Kiener, Daniel (Materials Characterization, 2021)
Keywords: Nanoindentation; Nanostructured materials; Helium bubbles; Helium implantation; Swelling; kernfusionsrelevant

Tuning mechanical properties of ultrafine-grained tungsten by manipulating grain boundary chemistry - Wurmshuber, Michael; Jakob, Severin; Doppermann, Simon; Wurster, Stefan; Bodlos, Rishi; Romaner, Lorenz; Maier-Kiener, Verena; Kiener, Daniel (Acta Materialia, 2022)
Keywords: Mechanical properties; Nanoindentation; Atom probe tomography; Grain boundary segregation engineering; Ultrafine-grained metals; Smallscale testing; Tungsten; kernfusionsrelevant

Ultrafine-grained Tungsten by High-Pressure Torsion - Bulk precursor versus powder processing route - Wurmshuber, Michael; Doppermann, Simon; Wurster, Stefan; Kiener, Daniel (40th Riso International Symposium on Materials Science: Metal Microstructures in 2D, 3D and 4D, 2019)
Keywords: kernfusionsrelevant

Unraveling the orientation-dependent mechanics of dental enamel in the red-necked wallaby - Wilmers, Jana; Wurmshuber, Michael; Gescher, Christoph; Graupp, Celine-Michele; Kiener, Daniel; Bargmann, Swantje (Acta Biomaterialia, 2024)
Dental enamels of different species exhibit a wide variety of microstructural patterns that are attractive to mimic in bioinspired composites to simultaneously achieve high stiffness and superior toughness. Non-human enamel types, however, have not yet received the deserved attention and their mechanical behaviour is largely unknown. Using nanoindentation tests and finite element modelling, we investigate the mechanical behaviour of Macropus rufogriseus enamel, revealing a dominating influence of the microstructure on the effective mechanical behaviour and allowing insight into structural dependencies. We find a shallow gradient in stiffness and low degree of anisotropy over the enamel thickness that is attributed to the orientation and size of microstructural features. Most notably, M. rufogriseus’s modified radial enamel has a far simpler structural pattern than other species’, but achieves great property amplification. It is therefore a very promising template for biomimetic design.<br